A search for [xi]++cc → D+pK-π+ decays - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2019)
A search for the Xi(++)(cc) baryon through the Xi(++)(cc) -> D(+)pK(-)pi(+) decay is performed with a data sample corresponding to an integrated luminosity of 1.7 fb(-1) recorded by the LHCb experiment in pp collisions at a centre-of-mass energy of 13 TeV. No significant signal is observed in the mass range from the kinematic threshold of the decay to 3800 MeV/c(2). An upper limit is set on the ratio of branching fractions R = B(Xi(++)(cc) -> D(+)pK(-)pi(+))/B(Xi(++)(cc) -> A(c)(+) K- pi(+)pi(+)) with R < 1.7 (2.1) x 10(-2) at the 90% (95%) confidence level at the known mass of the Xi(++)(cc) state.
cc im Titel ist tiefgestellt, Plus- und Minuszeichen sind hochgestellt
The LHCb Collaboration: R. Aaij, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, A. Comerma-Montells, P. D'Argent, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-menzemer, J. Hu, M. Kecke, M. Kolpin, R. Kopecna, B. Leverington, H. Malygina, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov und 824 weitere
Gesehen am 07.04.2020